Traditional Arbitration Institutions and Conflict Resolution Approaches in Nigeria: The Efficiency and Rhetorical Fallacy (British Journal of Multidisciplinary and Advanced Studies, 2023)
Before the advent of colonialism and its attendant degradation of African culture, Africans have had a concrete knowledge about what conflicts are, what causes conflicts and how conflicts are resolved.  Prior to western education, the Africans have developed a robust knowledge about the dynamics of conflicts and they have had institutionalized means of resolving their conflicts. In the present dispensation, however, the phrase ‘Traditional Arbitration Institutions’ has been given prejudiced responses by the westerners who dominated the study of peace with their scholarly works and claimed a monopolized knowledge of peace. Premised on this background, this paper focuses attention on exposing the systematic knowledge of Africans about disputes and conflicts resolution, using Nigeria as area of study; the paper discusses the conceptual meaning of Traditional Arbitration Institutions (TAI) and conflict resolution; the study seeks to identify and examine the roles of Traditional Arbitration Institutions in promotion of conflict resolution in Nigeria society. In addition, it examines various Traditional Arbitration Institutions (TAI) conflict resolutions mechanism and approaches put in place in resolving disputes and conflicts in Nigeria. The research methodology employed in the study is mixed methods which involves qualitative and quantitative research technique. This work adopted Traditional Arbitration Theory. The paper observes that there is a need for engaging Traditional Arbitration Institutions in resolving community and industrial based disputes and separatist’s agitation in Nigeria. The paper concludes by recommending various Traditional Arbitration strategies that can be adopted to complement existing efforts of promoting peace and stability in Africa.